Optimizing Scholarship Selection: A Decision Support System Approach Using the Analytical Hierarchy Process - Agus Yusuf Novianto (TIERS Information Technology Journal, 2023)
Scholarship is the provision of financial assistance to individuals, which aims to be used for the continuity of the education pursued. Per the scholarship provider's regulations, criteria are needed to determine who will be selected to receive the scholarship. Scholars are distributed by schools or other parties that organize scholarships to help someone who is underprivileged or who has achieved something during his studies. A decision support system is needed to help determine someone who deserves a scholarship. This system can analyze academic performance, financial needs, extracurricular activities, and personal statements to determine the most deserving candidates. By using a decision support system, scholarship providers can ensure that the scholarships are given to individuals who benefit the most from the financial assistance and are dedicated to their education. Ultimately, scholarships aim to help individuals overcome financial barriers and achieve their academic and career goals.